2016
DOI: 10.1002/jsfa.7773
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, mechanical, barrier and properties of films based on acetylated starch and cellulose from barley

Abstract: The mechanical, barrier, solubility, and thermal properties are factors which direct the type of the film application in packaging for food products. The films elaborated with acetylated starches of low degree of substitution were not effective in a reduction of the water vapor permeability. The addition of the cellulose fiber in acetylated and native starches films can contribute to the development of more resistant films to be applied in food systems that need to maintain their integrity. © 2016 Society of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Thickness is an important parameter as it is considered in the calculation of mechanical and barrier properties of films . Thickness of native and modified starch composite films is presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thickness is an important parameter as it is considered in the calculation of mechanical and barrier properties of films . Thickness of native and modified starch composite films is presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The miscibility of film‐forming components and homogeneity of films are well defined by the presence of a single endothermic peak . This endothermic peak is associated with the melting of starch crystals, which are rearranged during the process of retrogradation . It has been reported that the melting endotherm of starch films could originate from the co‐crystallization of amylose and amylopectin during the process of film formation, allowing continuous crystallization of amylopectin .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface and cross‐section morphology of the films were visualized using a scanning electron microscope (JEOL, JSM‐6610LV, Peabody, MA, USA), following the method described by Halal et al . Samples were examined at 1500× and 500× magnifications.…”
Section: Methodsmentioning
confidence: 99%